(untitled) (CIPEEX, 2025)
The present study aims to identify whether the limitation of places for women to enter military police careers is supported by the Federal Constitution of 1988. Firstly, the construction of gender inequality was contextualized, with the aim of analyzing the evolution of women’s rights over the years. It was demonstrated that even though Brazil is a Democratic State governed by the rule of law, governed by the principles of equality and human dignity, there are still limitations on access for women in several areas. Next, the problem of limiting the number of places for women in military police competitions was presented. Finally, a thorough analysis was made of the principles that govern the Democratic Rule of Law. Through the method of bibliographical review, based on the analysis of doctrines, related scientific articles, as well as relevant legislation with a main focus on the Brazilian Magna Carta, it was possible to conclude that the distinction made in the infra-constitutional legislation is opposed to the constitutional text in force in Brazil. In other words, it was concluded that limiting women’s access to police positions has no legal basis and contradicts the constitutional dictates of non-discrimination based on sex.